(untitled) (Bangladesh Journal of Microbiology, 2008)
The present study reports on the impact of Mycoplasma gallisepticum (MG) vaccination on vaccine respond and subsequent protection against Newcastle disease (ND) in parent stock flocks of Department of Livestock Services (DLS) using MG killed vaccine and conventional ND vaccines. Birds were grouped into four groups, each consisted of 50 birds from the same flock. Group A birds were vaccinated with ND, group B with ND and MG, group C with MG, and group D birds were kept as unvaccinated control. The parameters studied included detection of ND antibody, MG seroprevalance, mortality (%), and cause of death. The sera of groups B and C were sero-positive after administration of MG vaccine. The haemagglutination-inhibition (HI) titres of group A were higher than group B from week 4 after administration of MG vaccine to the birds of group B. The mortality was very low; one bird of group C died at week 5 due to traumatic injury and another bird of group D died at week 2 due to infectious bronchitis virus (IBV). After challenge, birds of groups A and B showed no clinical signs and normal post mortem findings were found. Birds of groups C and D showed clinical signs from day 3 and different pathological lesions were found in post mortem. The MG vaccination did not improve other parameters. Therefore, inoculation of MG INAC vaccine is not justified and is too expensive at farm levels. Keywords: Mycoplasma gallisepticum (MG) vaccine, Newcastle disease (ND) vaccination, Protection, Mortality DOI: http://dx.doi.org/10.3329/bjm.v24i1.1240 Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 62-64